Effect of Adding Fly Ash and Rice Husk Ash on Compressive Strength to Meet the fc'35 MPa Concrete Quality - Mardiaman Mardiaman; Hikma Dewita (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
Portland cement usage has increased, leading to substitute materials being sought. The composition of the concrete mix material affects its strength. Concrete compressive strength is usually determined in 7, 14, 21 and 28 days. This study determined the compressive strength of concrete at variations of 28, 35, 42 and 49 days. The attained compressive design strength was fc'35 MPa from the variation of the mixed materials. The compressive test results based on the variation were above fc'35 MPa. The two substitute materials meet the strength requirements. The addition of fly ash and rice husk ash decreased the compressive strength of concrete at 28 days. The compressive strength of regular concrete and with additional materials is more than 35 MPa. Adding fly ash and rice husk ash by 20% still resulted in the compressive strength of concrete above 35 MPa, namely 36.78 MPa and 35.04 MPa.